2018
DOI: 10.1523/jneurosci.3251-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mesocorticolimbic Connectivity and Volumetric Alterations inDCCMutation Carriers

Abstract: The axon guidance cue receptor DCC (deleted in colorectal cancer) plays a critical role in the organization of mesocorticolimbic pathways in rodents. To investigate whether this occurs in humans, we measured (1) anatomical connectivity between the substantia nigra/ventral tegmental area (SN/VTA) and forebrain targets, (2) striatal and cortical volumes, and (3) putatively associated traits and behaviors. To assess translatability, morphometric data were also collected in -haploinsufficient mice. The human volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
(23 reference statements)
5
20
0
Order By: Relevance
“…The associations between DCC and psychiatric disorders might be a consequence of DCC-related alterations to mesocorticolimbic pathways. As predicted, our group revealed that DCC haploinsufficient members of the Quebec family, as compared with control groups without the mutation (i.e., both relatives and unrelated healthy volunteers) exhibit striking reductions in anatomical connectivity, assessed using diffusion MRI probabilistic tractography, from the SN/VTA to both the ventral striatum and ventral mPFC [79].…”
Section: Haploinsufficiency: Dopamine Mesocorticolimbic Connectivitysupporting
confidence: 82%
See 4 more Smart Citations
“…The associations between DCC and psychiatric disorders might be a consequence of DCC-related alterations to mesocorticolimbic pathways. As predicted, our group revealed that DCC haploinsufficient members of the Quebec family, as compared with control groups without the mutation (i.e., both relatives and unrelated healthy volunteers) exhibit striking reductions in anatomical connectivity, assessed using diffusion MRI probabilistic tractography, from the SN/VTA to both the ventral striatum and ventral mPFC [79].…”
Section: Haploinsufficiency: Dopamine Mesocorticolimbic Connectivitysupporting
confidence: 82%
“…The DCC haploinsufficient Quebecers have an adult behavioral phenotype that shares two striking features with adult Dcc haploinsufficient mice [79]. First, the adult DCC haploinsufficient humans exhibit reduced novelty seeking personality traits [79]. Second, compared with their unaffected relatives, the DCC haploinsufficient humans smoke less tobacco yet use similar amounts of alcohol and cannabis [79], consistent with the evidence in mice that DCC's effects are specific to stimulant drugs.…”
Section: Haploinsufficiency: Personality Traits and Drugrelated Bsupporting
confidence: 59%
See 3 more Smart Citations